Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Guru Sekolah Menengah Atas - Susanty S, Dewi; Purba, Sukarman; Rosnelli, Rosnelli; Lubis, Zuraidah (CV. Rayyan Dwi Bharata, 2025)
This study aims to prove the influence of transformational leadership style, work mo- tivation, and job satisfaction both individually and collectively on the performance of elementary school teachers in Selayang District, Pemalang Regency. This is a quan- titative study using a cross sectional approach and an explanatory survey. Data were collected using a questionnaire with a Likert scale that has been tested for val- idity and is proven valid and stable. The results of the analysis prerequisite test in- cluding normality test, multicollinearity, heteroscedasticity, and linearity show that the requirements have been fulfilled. The result of the F test count is 120.311 with a significance value of 0.0000.05, meaning that there is a significant and positive ef- fect of transformational leadership style, work motivation, and job satisfaction on teacher performance. Partial test shows that the significance value of transforma- tional leadership style is 0.001, work motivation is 0.000, and job satisfaction is 0.0000.05, meaning that transformational leadership style, work motivation, and job satisfaction have a significant and positive effect on teacher performance, re- spectively. It shows that all hypotheses in this study are acceptable, which means that there is a positive and significant effect of transformational leadership style, work motivation, and job satisfaction both individually and collectively on the teachers’ performance.